THE QUALITY OF BAKTERIOLOGIS STUDY AND USE OF WATER OR DUG WELLS WITH AN OCCURRENCE WATER BORNE DISEASES IN THE VILLAGE WEST PASAYANGAN - Agustina, Norsita; Hayati, Ridha; Iriyanti, Hilda (Preventif : Jurnal Kesehatan Masyarakat, 2018)
Background & Objective : Clean water which could cause bakteriologis water quality ineligible .This studyattempts to know the quality of water bakteriologis a well (the bacteria MPN coliformm and e.coli )consumed villagers west Pasayangan Kabupaten Banjar in the water borne disease and relations the behaviorof the people in the water borne disease. Materials and method: This research methods used the crosssectional. The study analyzed by the quality of bakteriologis (MPN coliform and E. Coli ) as many as 30 awell. Data obtained through observation, interview using a questionnaire and results laboratory.Resultsbakteriologis water quality a well suggests that the whole water a well ineligible clean water developed bythe minister of health no. 416 / menkes / per / ix / 1990. Result: The results showed that source of drinkingwater and management of drinking water had links scene water borne disease. Conclusion: The quality ofbakteriologis well water dig they did not qualified drinking water and there was a correlation between theclean and healthy living (PHBS) in a household with a water borne diseases .Was recommended to thecommunity to need to do and healthy patterns of living water management well with the way of chlorine inand cook water with the right way before use.